2021
DOI: 10.1093/ndt/gfab287
|View full text |Cite
|
Sign up to set email alerts
|

Adipose expression of miR-130b and miR-17-5p with wasting, cardiovascular event and mortality in advanced chronic kidney disease patients

Abstract: Background There were limited data on the association of adipose microRNA expression with body composition and adverse clinical outcomes in patients with advanced chronic kidney disease (CKD). We aimed to evaluate the association of adipose miR-130b and miR-17–5p expressions with body composition, functional state, cardiovascular outcome and mortality in incident dialysis patients. Methods We performed a single-centre prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Chan et al demonstrated that miRNA-130b expression in adipose tissue decreased from nonfrail to severe frailty (1.01-fold vs. 0.32-fold, p=0.031) and predicted frailty independent of age and serum albumin level in patients with advanced chronic kidney disease. 34 It is tempting to conduct in-depth investigations of miRNA perturba-tion, adipose tissue distribution, and frail phenotype in the context of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al demonstrated that miRNA-130b expression in adipose tissue decreased from nonfrail to severe frailty (1.01-fold vs. 0.32-fold, p=0.031) and predicted frailty independent of age and serum albumin level in patients with advanced chronic kidney disease. 34 It is tempting to conduct in-depth investigations of miRNA perturba-tion, adipose tissue distribution, and frail phenotype in the context of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…19) Another study showed that adipose microRNA expression (MiR-130b) predicted frailty and incidence of MACE in advanced CKD patients. 20) Low BMI is due to various factors, such as malnutrition, chronic inflammation, cachexia, or frailty. The prevalence of frailty and prefrailty in hospitalized elderly patients with multimorbidity was high.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124-3p, a tumor-suppressive miRNA that targets CRKL, suppresses HCC carcinogenesis [ 102 ]. Adipose miR-130b and miR-17-5p expression in severe patients with CKD were linked to body composition characteristics, frailty, and predicted cardiovascular events and death [ 103 ]. Wang et al discovered miR-130b as a possible biomarker for OB, hypertriacylglycerolemia, and metabolic disease [ 98 ].…”
Section: Discussionmentioning
confidence: 99%